Pattern and distribution of lung parenchymal changes in COVID-19 infection on high resolution computed tomography: a descriptive cross-sectional study - Jose, Joe; Kalenahalli, Kiran V.; Yerram, Sravanthi; Itagi, Rishikesh M.; Eswara, Sowmya (International Journal of Research in Medical Sciences, 2022)
Background: This was a descriptive cross-sectional study conducted in a tertiary care hospital in south India during the peak of the COVID-19 infection pandemic in India between June 2020 to June 2021. HRCT lung parenchymal findings of patients with COVID-19 infection were studied, and the pattern and distribution of various lung parenchymal changes in each lung were described. HRCT lung findings were further correlated with clinical findings and clinical severity, which further helped in the clinical management of patients. Methods: This descriptive cross-sectional study was done at Sagar Hospitals, Tilak Nagar, Jayanagar, Bengaluru on a total of 111 RT-PCR positive COVID-19 patients in the age group 18 to 80. HRCT lung imaging findings were studied from June 2020 to June 2021 during the pandemic. These findings were further correlated with clinical findings and the clinical severity of the patient. Results: This study showed that chest CT findings in COVID-19 infection are variable. Ground glass opacity was the most common lesion observed, followed by Air space opacification and consolidation with an air bronchogram. In some cases, a crazy-paving pattern, subpleural linear bands, subpleural reticulations and fibrotic streaks were observed. A few cases showed traction bronchiectasis due to adjacent lung fibrosis and lung cyst within lesions. The lesion distribution was both bilateral (more common) and unilateral and showed peripheral predominance. There was a positive correlation between the CT severity score and clinical grading and the clinical severity of the patient. Conclusions: HRCT lung findings in COVID-19 patients were described in detail, including predominant lesion, predominant pattern, distribution in detail with reference to each lung segment, laterality, and correlation with clinical severity.